Перспективи розвитку транскордонного співробітництва України та Білорусі - Міцюк, І.; Mitsiuk, I.R. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Modern Ukrainian and Belarus cross border cooperation and the main factors of these collaboration have being researched. The problems of function euroregion «Buh» and the results of Cross-border Cooperation Programme Poland - Belarus - Ukraine 2007 2013 were analyzed. Problems and prospects of this cooperation have being submitted.
The prospects of cross border cooperation between Ukraine and Belarus
Міцюк І., студентка 43 групи факультету міжнародних відносин Східноєвропейського національного університету імені Лесі Українки Науковий керівник: к.і.н., доц.кафедри країнознавства і міжнародних відносин СНУ ім. Лесі Українки Моренчук А.А. (Україна, м.Луцьк)
Keywords: cross border cooperation; Ukrainian and Belarus cross border region; euroregion «Buh»; economic indicators; prospects of cooperation